Roberto Esposito and the Biopolitics of Property Rights. (September 2015) - Stone, Matthew
The nexus between property and subjectivity is at stake in various pressing contemporary debates, two of the most pertinent being on the separation of human body material into the status of property, and on the rapidly changing ways we think of virtual entities and places in proprietary terms. This intersection of questions of ownership and of personhood has naturally provoked a necessary discussion on the biopolitics of property. This article seeks to examine Roberto Esposito's reflections on property in order to develop a claim that there is a biopolitical mechanism not merely intrinsic to contemporary legal property relations but also rooted in the very structure of orthodox property theory that may be identified in the likes of Locke, Hegel and Kant. His work in this area allows us to understand the contradictions embedded within the liberal model of property rights as well as the scale of the intellectual challenge present in reimagining a more radical relationship between property and the subject.